Intravitreal anti-vascular endothelial growth factor, laser photocoagulation, or combined therapy for diabetic macular edema: A systematic review and network meta-analysis - Chen, Jiasheng; Wang, Haowei; Qiu, Weiqiang (Frontiers in Endocrinology, 2023)
Abstract Purpose: To conduct a network meta-analysis (NMA) comparing the efficacy of anti-vascular endothelial growth factor (VEGF) therapy alone versus laser photocoagulation (LP) therapy alone or anti-VEGF therapy combined with LP therapy for diabetic macular edema (DME). Methods: PubMed, Embase, Web of Science, and Cochrane Central Register of Controlled Trials were systematically searched for studies comparing anti-VEGF therapy alone versus LP therapy alone or anti-VEGF therapy combined with LP therapy for DME. Primary outcomes were mean best-corrected visual acuity (BCVA) and central macular thickness (CMT) change. Relevant data were collected and pooled using NMA. Results: A total of 13 randomized controlled trails were included in our NMA. Anti-VEGF therapy significantly improved BCVA the most compared to the combined (mean difference [MD] = 1.5; 95% confidence interval [CI]: 0.084, 2.7) and LP (MD = 6.3; 95% CI: 5.1, 7.6) therapies at six months, while there was no difference in reducing CMT at six months between the anti-VEGF and combined therapies (MD = -16; 95% CI: -46, 13). At 12 months, no significant difference was found between the anti-VEGF and combined therapy in terms of BCVA (MD = 0.1; 95% CI: -1.7, 1.5) and CMT (MD = 21; 95% CI: -3.0, 44). Conclusion: There was no significant difference between the anti-VEGF therapy and combined therapy. For the long-term treatment of patients with DME, combined therapy is recommended.